The Effect of the Contextual Teaching and Learning (CTL) Model on the Indonesian Language Learning Outcomes of Third-Grade Students at SDN 10 Pulau Punjung - Zumrotun Lutfiah; Ahmad Ilham Asmaryadi; Vioni Agustira Anggraini (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the low learning outcomes of third-grade students in Indonesian language subjects, the lack of student attention and active participation during learning activities, the limited use of varied learning models, and the insufficient facilities and infrastructure that support the learning process. In the Indonesian language learning process, there is a discrepancy between expectations and reality. The aim of this study is to examine the effect of the Contextual Teaching and Learning (CTL) model on the Indonesian language learning outcomes of third-grade students at SDN 10 Pulau Punjung. This study is an experimental research employing a quasi-experimental design, specifically using the nonequivalent control group design. The research was conducted at SDN 10 Pulau Punjung. The population of this study includes all students in Class III/A and Class III/B. The sample consists of 29 students: 14 from Class III/A and 15 from Class III/B. The data collection technique used in this study is a test in the form of objective questions. The results show that the average post-test score of the control class was 80, while the experimental class scored an average of 87.2. The normality test resulted in significance values of 0.182 for the control class and 0.097 for the experimental class, indicating that both classes are normally distributed. The homogeneity test yielded a significance value of 0.957. The hypothesis testing using the Independent Samples Test showed a significance value of 0.025. Since 0.025 < 0.05, the result of the Independent Samples Test indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It can be concluded that there is a significant effect of implementing the Contextual Teaching and Learning (CTL) model on the Indonesian language learning outcomes of third-grade students at SDN 10 Pulau Punjung.